ACUTE DIARRHEA IN CHILDREN - T.S. Lazareva ("Paediatrician" Publishers LLC, 2008)
Acute diarrhea in children is a vital issue in pediatric practice. Diseases with diarrhea syndrome are widely disseminated; they have a tendency to chronicity and frequent relapse. Besides, irrational antibacterial treatment in children is a frequent cause of diarrhea. Diarrhea may be one of first symptoms of dyspepsia, which development is caused by anatomico-physiological features of gastrointestinal tract of children and mistakes in nutrition. The management of diarrhea syndrome is based on the principles of elimination of causative agent and correction of nutrition. Dietary cure, rehydration and enter sorbents are used in more severe cases. Intestinal micro biocenosis recovery is advisable in children on artificial feeding.Key words: children, acute diarrhea, treatment.